Exploring the Use of Learning Management System Features in Higher Education Learning - Dedy Aswan (Jurnal Ilmiah Wahana Pendidikan, 2026)
The rapid adoption of digital technologies in higher education has increased the use of Learning Management Systems (LMS) to support teaching and learning activities. However, the extent to which students utilize the various features available within LMS platforms remains insufficiently understood. This study aimed to analyze the utilization of different LMS features in student learning activities. A quantitative descriptive research design was employed involving 102 university students who had actively used an LMS for at least one semester. Data were collected through an online questionnaire developed based on four LMS dimensions: learning content, communication, assessment, and learning monitoring. The instrument demonstrated good reliability with a Cronbach’s Alpha coefficient of 0.87. Data were analyzed using descriptive statistics, including mean and standard deviation. The findings revealed that LMS features related to learning content, assessment, and learning monitoring were utilized more frequently than communication features. Assignment submission (M = 4.41), learning materials (M = 4.32), and grade monitoring (M = 4.30) were identified as the most frequently used features. In contrast, chat (M = 1.88) and discussion forums (M = 2.54) showed the lowest levels of utilization. These results indicate that students primarily use LMS platforms as tools for accessing learning resources, completing assessments, and monitoring academic progress rather than as environments for communication and collaboration. The study highlights the need for higher education institutions and instructors to optimize communication-oriented LMS features to enhance student interaction and engagement in digital learning environments.